Social Interactions and Status Markers in the Roman World. - Cupcea, George.
1 online resource (182 pages)
Keywords: Proceedings from the 'People of the Ancient World' conference held in Cluj-Napoca, Romania in 2016. Ten papers encompass diverse approaches to Roman provincial populations and the corresponding case-studies highlight the multi-faceted character of Roman society.